2021
DOI: 10.3389/fpls.2021.581127
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Deficit and Fertilizer Placement Effects on Root Biomass Distribution, Soil Water Extraction, Water Use, Yield, and Yield Components of Soybean [Glycine max (L.) Merr.] Grown in 1-m Rooting Columns

Abstract: Typical small-pot culture systems are not ideal for controlled environment phenotyping for drought tolerance, especially for root-related traits. We grew soybean plants in a greenhouse in 1-m rooting columns filled with amended field soil to test the effects of drought stress on water use, root growth, shoot growth, and yield components. There were three watering treatments, beginning at first flower: watered daily to 100% of the maximum soil water holding capacity (control), 75% (mild drought stress), or 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 62 publications
4
20
2
Order By: Relevance
“…Water availability in the field can decrease dramatically with extreme high temperatures that increase water evaporation from the soil surface [4]. Water deficit decreases crop growth, development, yield, and yield components of grain legumes [5][6][7]. The extent of the yield reduction depends on the duration and intensity of the stress and varies between species and cultivars and climatic variations, as reported for mungbean, soybean, and grass pea [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water availability in the field can decrease dramatically with extreme high temperatures that increase water evaporation from the soil surface [4]. Water deficit decreases crop growth, development, yield, and yield components of grain legumes [5][6][7]. The extent of the yield reduction depends on the duration and intensity of the stress and varies between species and cultivars and climatic variations, as reported for mungbean, soybean, and grass pea [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit decreases crop growth, development, yield, and yield components of grain legumes [5][6][7]. The extent of the yield reduction depends on the duration and intensity of the stress and varies between species and cultivars and climatic variations, as reported for mungbean, soybean, and grass pea [6][7][8][9][10]. Reduced soil water content to a moderate drought level (60% field capacity) reduced pod and seed numbers and seed yield per plant in mungbean (line 97001) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have explored various fertilization management practices for improving crop productivity ( Liu et al, 2015 ; Su et al, 2015 ; Gebre and Earl, 2021 ; Zhong et al, 2021 ). In particular, compared with broadcasting or mixing fertilizer, banding fertilizer in the soil can improve the NUE and crop yield in rice ( Liu et al, 2015 ; Zhong et al, 2021 ), rape ( Su et al, 2015 ), soybean ( Gebre and Earl, 2021 ), wheat ( Singh et al, 2005 ), and maize ( Cheng et al, 2020 ; Wu et al, 2021 ). Therefore, banding fertilizer has some advantages for promoting crop production.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages are mainly due to banding fertilizer improving the availability of nutrients in the crop root zone to promote the growth and function of roots. Banding fertilizer in the root zone is an effective fertilization method and it has attracted much attention from researchers ( Liu et al, 2015 ; Su et al, 2015 ; Gebre and Earl, 2021 ). Su et al (2015) showed that fertilization at soil depths of 10 and 15 cm increased the taproot length and dry weight compared with depths of 0 and 5 cm.…”
Section: Introductionmentioning
confidence: 99%
“…However, since soybean is cultivated mostly under rainfed conditions, soybean production is severely constrained by abiotic stresses, particularly drought (5). Even mild drought stress that occurs without obvious outward signs of a stress response such as leaf wilting poses a major threat to soybean productivity (6). Given that strategies to increase arable land area and yield face major obstacles, identifying ways to reduce crop production losses due to mild drought stress is a key goal in attaining global food security.…”
Section: Introductionmentioning
confidence: 99%